PERBANDINGAN KADAR TROMBOSIT PADA DARAH VENA DAN KAPILER MENGGUNAKAN ANTIKOAGULAN K3EDTA - Franciscus Deni Suryatama; Rosnita Sebayang; Hutabarat, Mustika (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Selection of the wrong type of examination sample can affect the results of the examination. Examination of blood cell counts can be taken from venous blood and capillary blood, but in capillary blood sampling there can be a dilution of the blood by tissue fluid so that the results of the blood cell count allow for differences between capillary blood samples and venous blood. The purpose of this study was to determine the difference in the number of platelets in venous blood and capillary blood in a hematology analyzer. This type of research is descriptive-analytic. Examination using Sysmex KX-21 with Blood Cell Counter method. All data were tested for normality using Shapiro-Wilk and hypothesis testing using Independent Sample T Test. The results of the examination showed a significant difference, where the platelet count of the capillary blood was lower than that of the venous blood and statistically showed a significant difference in the number of platelets with a value of =0.01 (<0.05). So it can be concluded that there are differences in the number of platelets in venous blood and capillary blood.